Electronic games and suicide: The blue whale game as an example - Boucenna, Abdelwafi Zoheir (Journal of Human Sciences, 2024)
The blue fish is an electronic game that has been on social media since 2016-2019. This may also be the case for adolescents who suffer from death to let the suicider reach the end. This article proposes to display the color of blue hair and its content and other effects on adolescent parents and your family.